2022
DOI: 10.1002/jgh3.12738
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic features of colorectal lymphoma according to histological type

Abstract: Background and Aim This study aimed to investigate the relationship between the histological type of colorectal lymphoma and its endoscopic features. Methods We retrospectively analyzed patients with primary colorectal lymphoma who were diagnosed using colonoscopy and biopsy specimens at the National Cancer Center Hospital, Tokyo, Japan. The lesions were macroscopically classified into the following types via colonoscopy: polypoid, ulcerative, multiple lymphomatous polyposis, diffuse, and mixed. Results A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…In our study, colorectal DLBCL lymphomas manifested as a protruding type with or without ulcer (which was consistent with the polypoid type). This was similar to a study by Yachida that reported that in 48 cases of DLBCL lymphoma in the large intestine, and 52% of lesions showed a polypoid appearance via endoscopy, and 38% were of the ulcerative type [37]. Yoshifumi Hori also found that the polypoid and ulcerative types were predominant in colorectal DLBCL lymphomas, accounting for 48% and 44%, respectively [30].…”
Section: Endoscopic Features Of Diffuse Large B Cell Lymphoma (Dlbcl)supporting
confidence: 89%
See 1 more Smart Citation
“…In our study, colorectal DLBCL lymphomas manifested as a protruding type with or without ulcer (which was consistent with the polypoid type). This was similar to a study by Yachida that reported that in 48 cases of DLBCL lymphoma in the large intestine, and 52% of lesions showed a polypoid appearance via endoscopy, and 38% were of the ulcerative type [37]. Yoshifumi Hori also found that the polypoid and ulcerative types were predominant in colorectal DLBCL lymphomas, accounting for 48% and 44%, respectively [30].…”
Section: Endoscopic Features Of Diffuse Large B Cell Lymphoma (Dlbcl)supporting
confidence: 89%
“…In addition, not all cases of lymphomatous polyposis of the digestive tract are caused by MCL. Multiple lymphomatous polyposis has also been observed in MALT and follicular lymphomas [37,53].…”
Section: Endoscopic Features Of Mantle Cell Lymphomas (Mcl)mentioning
confidence: 99%
“…However, relevant studies about ITCL are rare due to low incidence and lack of endoscopic findings specificity. The few existing studies have reported the most common endoscopic abnormalities in intestinal lymphoma are the ulcerated lesion followed by eminence lesion, in addition to the diffusely infiltratively lesion and lymphomatous polyposis lesion et al [12][13][14] Ulcerated lesions may present multiple or solitary, various in size, different in shades, irregular in shape, the edges are flat or irregularly thickened. Yet those performance is often misdiagnosed as inflammatory bowel disease.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to take into consideration the endoscopic and clinical presentations[ 19 ]. Endoscopic findings are nonspecific, ranging from a single polypoid lesion to a subepithelial tumour type, an epithelial mass type, and an ileitis type[ 14 ]. EUS is an accurate technique for evaluating the extent and invasion of the lesion.…”
Section: Discussionmentioning
confidence: 99%